2014
DOI: 10.1155/2014/742432
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation and Large Eddy Simulation on a Turbulent Wall-Bounded Flow Using Lattice Boltzmann Method and Multiple GPUs

Abstract: Direct numerical simulation (DNS) and large eddy simulation (LES) were performed on the wall-bounded flow atReτ=180using lattice Boltzmann method (LBM) and multiple GPUs (Graphic Processing Units). In the DNS, 8 K20M GPUs were adopted. The maximum number of meshes is6.7×107, which results in the nondimensional mesh size ofΔ+=1.41for the whole solution domain. It took 24 hours for GPU-LBM solver to simulate3×106LBM steps. The aspect ratio of resolution domain was tested to obtain accurate results for DNS. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…For the temporal discretization of formula (20), the method of lines is used, such that space and time integration can be handled separately. Space integration, which consists of the solution of convective fluxes and viscous fluxes, is introduced hereinbefore.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…For the temporal discretization of formula (20), the method of lines is used, such that space and time integration can be handled separately. Space integration, which consists of the solution of convective fluxes and viscous fluxes, is introduced hereinbefore.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Khajeh-Saeed et al [19] accomplished direct numerical simulation (DNS) of turbulence using GPU accelerated supercomputers, which demonstrated that scientific problems could benefit significantly from advanced hardware. Wang et al [20] discussed DNS and Large Eddy Simulation (LES) on a turbulent wall-bounded flow using Lattice Boltzmann method and multiple GPUs, and the acceleration performance has been discussed. Emelyanov et al [21] discussed the popular CFD benchmark solution of the flow over a smooth flat plate on a GPU with various meshes, and the speedup reached more than 46 times.…”
Section: Introductionmentioning
confidence: 99%
“…Lai and Khan [9] adopted the message-passing interface (MPI) method to develop a parallel two-dimensional discontinuous Galerkin method for shallow-water flows. Since the multi-CPUs provided by supercomputers are relatively expensive, the more cost-effective computation platform based on a personal computer with a graphics processing unit (GPU) card could be used for fast simulation of large-scale floods, regarding the development that now one GPU card integrating thousands of computing cores can provide a powerful computational capability [10]. For example, Wang and Yang [11] adopted the GPU-based, high-performance-integrated hydrodynamic modelling system to simulate flood processes at the basin scale.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the parallel algorithms, GPU models obtain the best acceleration [21][22][23]. The multistreaming processors and powerful computational capabilities of GPUs are vitally important for efficient parallel computation with large amounts of data and high-precision requirements [24][25][26][27][28]. Bradbrook et al [29] rewrote the twodimensional diffusive wave model JFLOW using generalpurpose GPUs and achieved substantially faster computation on single-accelerator processors.…”
Section: Introductionmentioning
confidence: 99%